THE INFLUENCE OF THE ADDITION OF FLOUR LEAVES KELOR IN FEED TO CREATININ LEVELS AND UREA SERUM MICE WISTAR - Dosom, Yoviniani Narti; Suarsana, I Nyoman; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2018)
Plants kelor ( moringa oleifera ) has long best known to the public and has long been also used in traditional medicines and consumed as a vegetable and fodder for cattle. Flour leaves kelor itself has several substances hypotensif, anticancer, antioxidant, and antibakterial. This research aims to understand the influence of the addition of flour leaves kelor against creatinin levels and urea mice wistar blood. Sample used is 20 the tail of a mouse white galur wistar ( rattus novergicus ) the was 1-1,5 the moon and have weight 50-80 grams. Twenty the tail of a mouse wistar was divided into 5 the treatment group. The group differentiated based on concentration flour leaves kelor namely 0 %, 2.5 %, 5 %, 10 %, and 20 %. Data creatinin levels and urea analyzed use fingerprint variety of (ANOVA). If the real effect of treatment followed by Duncan test at 5% confidence level. The result of this research is on concentration 5 % creatinin levels decreased compared to the control group. In the 2.5 %, 10 % and 20 % have been kenaikan compared to the control group, but about 10 % lower than the 2,5 % and 20 %. While, on levels of urea group rtas serum a dose of 2,5 % and 5 % has experienced a fall in compared with the control group. Group 10 % an 20 % increased compared and control groups a dose of 10 % increasing significant.